Hubungan Status Gizi, Aktivitas Fisik Dan Konsumsi Junk Food Dengan Keteraturan Siklus Menstruasi Pada Remaja Putri Di SMP Negeri 2 Kota Malang - Iva Sulistya; Anindya Hapsari; Hartati Eko Wardani (Jurnal Medika Nusantara, 2023)
Menstruation is the discharge of blood due to the shedding of the endometrial wall. The menstrual cycle is the time span between the first of menstruation and the first of the next menstruation. It’s said to be normal if the time gap is 21-35 days. Irregularity of the menstrual cycle as a sign of reproductive diseases, stress, homon imbalance, inadequate nutritional intake and even infertility. The frequency of menstrual cycle irregularities was 69.2%. The increasing prevalence of menstrual cycle disorders is caused by stress, disease, hormonal imbalance, physical activity, lifestyle, and nutritional status. Objective: To investigate the relationship between nutritional status, physical activity, consumption of unhealthy foods and regularity of menstrual cycle among young women in SMP Negeri 2 Malang City. Study type: Quantitative correlation with a cross-sectional method. Time and place: May 2023 at SMPN 2 Malang City. The main population of class VIII is 185 people out of which 65 students used simple probability sampling technique. A questionnaire was used as a research instrument. The results of correlation analysis using Spearman's statistical test showed that there was a relationship between nutritional value and junk food consumption with menstrual regularity at P = 0.005 and 0.005 (p 0.05).